Clean-Induced Instability of Electrical Characteristics in Poly-Si Junctionless Nanowire Transistor. (1st January 2017) - Kang, Tsung-Kuei; Chen, Wei-Hao; Liu, Han-Wen; Chien, Feng-Tso; Lin, Cheng-Li; Wang, Fang-Hsing
Abstract : A heavy doped poly-Si junctionless channel immersed in NH4 OH/H2 O2 /H2 O (SC1) solution is always unexpectedly damaged and results in an instable electrical characteristic in a proposed tri-gated nanaowire (NW) thin film transistor (TFT). A new finding indicates that a sharp nanowire profile is observed because some segregated precipitates at the poly-Si grain boundaries are etched and the dependence of the silicon etch rate on the crystal orientation/grain size also impacts the sharp corner formation in SC1 solution. Moreover, it results in damaged nanowire surface and many electron traps in subsequently deposited gate oxide. Therefore, a smaller etching amount in SC1 solution is suggested in the fabrication of a tiny poly-Si junctionless nanowire TFT.